A New and Simple Method for Manufacturing Electrochromic Tungsten Oxide Films - N. G. Park; B. W. Kim; A. Poquet; G. Campet; J. Portier; J. H. Choy; Y. I. Kim (Active and Passive Electronic Components)
A new and simple method for the preparation of electrochromic tungsten oxide film is presented. This novel approach can be realized by introducing a nanoporous textured polyacrylic acid (PAA) layer between tungsten oxide layer and indium tin oxide (ITO) one by dip-coating process. Homogeneous film with a thickness of about 0.8 μm is made by single dipping a PAA-coated ITO glass in the WO3-NH4OH solution and shows an X-ray amorphous structure. During the cathodic and anodic processes by chronopotentiometry, the present films exhibit highly reversible electrochemical insertion of lithium ions; the corresponding inserted charge of 12.5 mC/cm2 gives rise to a marked blue color yielding the change in optical density (AOD) of 0.65 at 550 nm and a coloration efficiency (η) of 51.8 cm2/C.